IN VITRO STUDIES ON THE POTENTIALITY OF BALANITES OIL IN THE TREATMENT OF SOME SUPERFICIAL MYCOSES - Osman, Nour Ahmed; Elhussein, Salah Ahmed; Abdelrahman, Elnour Elamin; Hussein, Ismail Hassan; Mohamed Toum, Abdalla (Gezira Journal of Health Sciences; Vol 2 No 2 (2006), 2006)
Fruits of Balanites aegyptiaca are traditionally used in paste form for curing some skin diseases in few areas in Western Sudan Our initial results pointed to the fruit kernel containing the active ingredient. Further studies were meant to test, in vitro, the effect of Balanites fruit kernel oil on three isolates which are known to cause superficial mycoses namely: Microsporum audouinii, Trichophyton soudanense and T. mentagrophytes. The three test organisms were subcultured on sabouraud’s medium to which different concentrations of Balanites kernel oil were added. In addition to appropriate controls a normal vegetable oil viz. peanut oil, was tested. BKO, at 5% concentration, showed marked (>70%) growth inhibition against the three fungal isolates tested. No antifungal activity was observed in controls, including peanut oil. Two fractions of Balanites kernel oil were prepared namely: the free fatty acids (FFA) and the unsaponifiable matter (UM), and when tested for antifungal activity with the three test organisms, the activity resided exclusively in the free fatty acid fraction. Initial clinical studies on Balanites kernel oil, currently underway, largely confirmed our in vitro work described here.